1993
DOI: 10.1152/ajpcell.1993.264.3.c591
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-regulated whole cell chloride currents in pancreatic duct cells

Abstract: Using the whole cell configuration of the patch-clamp technique, we have identified an adenosine 3',5'-cyclic monophosphate (cAMP)-regulated chloride conductance in pancreatic duct cells. Basal whole cell currents in single isolated cells were very low (approximately 5 pA/pF) but could be stimulated 17-fold by elevation of intracellular cAMP. The cAMP-activated currents exhibited 1) a high chloride selectivity, 2) a near linear current-voltage relationship, 3) time and voltage independence, 4) block by 5-nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
1
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 15 publications
8
77
1
3
Order By: Relevance
“…The oocytes were then transferred into 1.4 ml of the following Cl Ϫ -containing solution: NaCl (100 mM), KCl (2 mM), CaCl 2 (1 mM), MgCl 2 (1 mM), NaHCO 3 (8 mM) bubbled with 1.5% CO 2 , pH 7.4. with 3.3 Ci of 36 Cl Ϫ . A 10-l aliquot was removed from the influx solution for later determination of 36 Cl Ϫ -specific activity. 36 …”
Section: CLmentioning
confidence: 99%
See 3 more Smart Citations
“…The oocytes were then transferred into 1.4 ml of the following Cl Ϫ -containing solution: NaCl (100 mM), KCl (2 mM), CaCl 2 (1 mM), MgCl 2 (1 mM), NaHCO 3 (8 mM) bubbled with 1.5% CO 2 , pH 7.4. with 3.3 Ci of 36 Cl Ϫ . A 10-l aliquot was removed from the influx solution for later determination of 36 Cl Ϫ -specific activity. 36 …”
Section: CLmentioning
confidence: 99%
“…A 10-l aliquot was removed from the influx solution for later determination of 36 Cl Ϫ -specific activity. 36 …”
Section: CLmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar model to explain HCO 3 -secretion by the pancreatic duct of non-rodent eutherian mammals has been proposed (Park et al, 2010;Steward et al, 2005). CFTR from eutherian mammals also has a relatively low P HCO3 (Gray et al, 1993;Gray et al, 1990;Linsdell et al, 1997;O'Reilly et al, 2000;Poulsen et al, 1994). However, in the pancreatic duct cells it has been suggested that HCO 3 -secretion occurs via CFTR because there is no mechanism on the basolateral membrane to accumulate Cl -, whereas there is a mechanism for HCO 3 -accumulation (Fernández-Salazar et al, 2004).…”
Section: Discussionmentioning
confidence: 88%